2008
DOI: 10.1002/icd.573
|View full text |Cite
|
Sign up to set email alerts
|

Making the most of information‐gathering interviews with children

Abstract: Because child abuse victims are often the only available sources of information about their experiences, extensive efforts have been made to understand how to maximize their informativeness. There is now broad international consensus regarding optimal interview practices, and broad awareness that children's informativeness increases when interviewers conduct developmentally appropriate interviews with children. In this paper, we (1) summarize current understanding of how children remember, retrieve, and commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 96 publications
(110 reference statements)
3
30
0
2
Order By: Relevance
“…An important issue is that young children provide relatively little information in free or open-ended recall (Pipe et al, 2006, Powell et al, 2005, and thus, interviewers are forced to obtain the vast majority of the information they seek through the use of more directive questions. Option-posing questions that rely on recognition memory rather than recall are particularly problematic, and of course, more directive questions provide more opportunities for leading, misleading, or suggestive questions (Larsson & Lamb, 2009). The NE technique provides a mechanism for encouraging open-ended recall by children and thus capitalizes on one of their strengths, namely, the accuracy of such recall.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An important issue is that young children provide relatively little information in free or open-ended recall (Pipe et al, 2006, Powell et al, 2005, and thus, interviewers are forced to obtain the vast majority of the information they seek through the use of more directive questions. Option-posing questions that rely on recognition memory rather than recall are particularly problematic, and of course, more directive questions provide more opportunities for leading, misleading, or suggestive questions (Larsson & Lamb, 2009). The NE technique provides a mechanism for encouraging open-ended recall by children and thus capitalizes on one of their strengths, namely, the accuracy of such recall.…”
Section: Discussionmentioning
confidence: 98%
“…Memory researchers have shown that such events are remarkably well remembered, even by 3-to 7-year-old children (see Peterson, 2002, for a review). Although young children recall a considerable amount of information about highly salient and unique events, the act of communicating what they recall is more problematic (Larsson & Lamb, 2009). An important issue is that young children provide relatively little information in free or open-ended recall (Pipe et al, 2006, Powell et al, 2005, and thus, interviewers are forced to obtain the vast majority of the information they seek through the use of more directive questions.…”
Section: Discussionmentioning
confidence: 99%
“…This could have important consequences in a real world context and for professional training. As pointed out by Larsson and Lamb (2009), police officers seem to have trouble to successfully and durably apply the recommendations found in the interview training manuals and lectures, and notably the instructions given to build the rapport with a child (Westcott & Kynan, 2006). Perhaps, informing the judicial practitioners, during training, about the decline in memory quantity associated to the omission of the social instructions, could help them to understand better the interest of using such instructions, and thus, to internalize better what they have learned during their training.…”
Section: Influence Of the Social Instructions On The MCI Effectivenesmentioning
confidence: 91%
“…If rumor can bring about errant beliefs about witnessing events that only were overheard, there is little that forensic interviewers can do to mitigate its effects. In contrast, if reports of rumored occurrences merely are driven by compliance to social pressures, such effects may be reduced by protocols that enhance the retrieval and reporting of information in memory, such as the Revised Cognitive Interview or the National Institute of Child Health and Human Development Investigative Interview (see Larsson & Lamb, 2009). The primary aim of the current study, therefore, was to examine the degree to which reports of rumored-but-nonexperienced events occur because children have come to believe they have seen the suggested occurrences, or simply reflect social demands to relay overheard information.…”
mentioning
confidence: 99%